How to research trends : move beyond trendwatching to kickstart innovation - Dragt, Els, ....- (Amsterdam : BIS Publishers, 2024)
Take a deep dive into the future with this book as your trusty companion. "How to Research Trends" shows you how to navigate and explore using the powerful tool of trend research. Learn how to scan the environment for signs of change, analyse trend spots, and apply insights to kickstart innovation. This revised edition is designed for professionals who want to incorporate trend research into their own work. It features new interviews with professionals and agencies, as well as new theories, including Shalom Schwartz's human values model and the futures consciousness model from the University of Finland. Learn how to use trend research to explore the future, and you'll be prepared for change and the uncertainties it brings.
Keywords: Marketing research; Marktonderzoek; Trends